Measuring market and inflation risk premia in France and in Germany - Lorenzo Cappiello; Stéphane Guéné (European Central Bank (ECB), 2005)
This paper studies the role of inflation in the determination of financial asset prices. We estimate an Intertemporal Capital Asset Pricing Model à la Merton (1973), with inflation as an independent source of risk, for France and Germany. Our study also allows us to evaluate how the different nature of the French and German monetary policies before 1999 as well as the convergence process towards the single currency might have affected the role of inflation in the pricing of financial assets. We find that inflation is a significant explanatory factor for the pricing of stocks and government bonds in the two countries. Moreover, while there seems to be no clear structural break in the impact of inflation on asset prices after Stage Three of Economic and Monetary Union, such an impact has been increasingly similar in the two countries after 1999.
Keywords: C32; C61; E44; G12; 330; business cycles; GARCH-in-Mean; Intertemporal CAPM; CAPM; Risikoprämie; Inflation; Schätzung; Frankreich; Deutschland